Increased Participation and Decreased Performance in Recreational Master Athletes in “Berlin Marathon” 1974–2019 - Reusser, Marlen; Sousa, Caio Victor; Villiger, Elias; Alvero Cruz, José Ramón; Hill, Lee; Rosemann, Thomas; Nikolaidis, Pantelis T.; Knechtle, Beat (Frontiers in Physiology, 2021)
The aspect of participation and performance trends in marathon running has been investigated mainly in marathons held in the United States of America (e.g. '‘New York City Marathon’, ‘Boston Marathon’), but not for the fastest course in the world, the ‘Berlin Marathon’ held in Berlin, Germany. This study aimed to examine trends in participation and performance in the ‘Berlin Marathon’ on all its previous 46 editions from 1974 to 2019, the largest dataset ever studied in this event with 696,225 finishers (after data cleaning). Athletes in all age groups increased their participation, except for male athletes aged 20-49 years and athletes of both sexes above 79 years of age. This overall increase in participation was more pronounced in women, but still, there are more men than women participating in ‘Berlin Marathon’ nowadays. All age group athletes decreased their performance across years overall, whereas the top ten recreational athletes improved their performance over the years. Our findings improved the knowledge about the evolution of male and female marathoners across calendar years, especially for the fastest marathon race in the world, the ‘Berlin Marathon’.